Neurodevelopment and physical measurements in infants with birthweight of 500 grams or less - Itoshima Ryo; Oda Arata; Ogawa Ryo; Yanagisawa Toshimitsu; Hiroma Takehiko; Nakamura Tomohiko (Australia, 2025)
Background: In infants born weighing ≤500 g, little has been studied about the association between neurodevelopmental prognosis and growth. This study aimed to evaluate the association between neurodevelopmental impairment (NDI) and z-scores of physical measurements in infants born weighing ≤500 g.
Methods: A single-center, retrospective cohort study in a level IV neonatal intensive care unit in Japan. Infants born weighing ≤500 g between 2010 and 2019 were eligible. Z-scores in weight, length/height, and head circumference at birth, due date (or discharge), 6 and 18 months of corrected age, and 3 years of age were compared between infants with and without NDI at 3 years of age. Three infants with severe intraventricular hemorrhage or periventricular leukomalacia were excluded from the comparison analyses. NDI was defined as having a developmental quotient of ≤70, cerebral palsy, visual impairment, or hearing impairment.
Results: Of 22 eligible infants, the incidence of NDI at 3 years of age was 54.5%. The z-score was significantly smaller in the NDI group (n = 10) than that in the non-NDI group (n = 9) in head circumference at birth (median, -1.94 vs. -0.75; Z = 0.54; p = 0.020), and in height at 18 months of corrected age (median, -2.84 vs. -1.79; Z = 0.58; p = 0.013) and 3 years of age (median, -2.02 vs. -1.21; Z = 0.47; p = 0.046).
Conclusions: NDI at 3 years of age was associated with a small head circumference z-score at birth, height at 18 months of corrected age, and height at 3 years of age in infants born weighing ≤500 g.